Transient global amnesia following deliberate self-harm by hanging: Case report and review - Jyoti Prakash (Wolters Kluwer Medknow Publications, 2021)
A 25-year-old female was hospitalized subsequent to an attempt to hang herself. She was unconscious for a few minutes but responded to initial resuscitative measures. Relevant investigations, including X-ray neck, computed tomography scan brain, and electroencephalogram were normal. Physical examination was consistent with attempted hanging. On mental status examination, speech was relevant. Mood was euthymic. Attention was arousable, but concentration was impaired. Orientation to time and recent memory were impaired. Remote memory, insight, and judgment were unimpaired. Serial Mental Status Examination (MSE) revealed improvement in concentration and orientation. Due to sudden onset memory loss of <24 h in duration without other signs of cognitive impairment or concomitant focal neurological symptoms, she was diagnosed as a case of transient global amnesia. The pathophysiology of the condition is briefly reviewed.